Mechanism of zonal disintegration phenomenon in enclosing rock mass around deep tunnels - Wu, Hao; Guo, Zhi-kun; Fang, Qin; Zhang, Ya-dong; Liu, Jin-chun (Journal of Central South University of Technology. Science & technology of mining and metallurgy, 2009)
In order to study the mechanism of the zonal disintegration phenomenon (ZDP), both experimental and theoretical investigations were carried out. Firstly, based on the similarity law, gypsum was chosen as equivalent material to simulate the deep rock mass, the excavation of deep tunnel was modeled by drilling a hole in the gypsum models, two circular cracked zones were measured in the model, and ZDP in the enclosing rock mass around deep tunnel was simulated in 3D gypsum model tests. Secondly, based on the elasto-plastic analysis of the stressed-strained state of the surrounding rock mass with the improved Hoek-Brown strength criterion and the bilinear constitutive model, the maximum stress zone occurred in vicinity of the elastic-plastic interface due to the excavation of the deep tunnel, rock material in maximum stress zone is in the approximate uniaxial loading state owing to the larger tangential force and smaller radial force, the mechanism of ZDP was explained, which lay in the creep instability failure of rock mass due to the development of plastic zone and transfer of the maximum stress zone within the rock mass. Thirdly, the analytical critical depth for the occurrence of ZDP was obtained, which depended on the mechanical indices and stress concentration coefficient of rock mass.